2019
DOI: 10.1021/acs.est.9b02166
|View full text |Cite
|
Sign up to set email alerts
|

Newly Identified AhR-Active Compounds in the Sediments of an Industrial Area Using Effect-Directed Analysis

Abstract: Effect-directed analysis was used to identify previously unidentified aryl hydrocarbon receptor (AhR) agonists in sediments collected from a highly industrialized area of Ulsan Bay, Korea. The specific objectives were to (i) investigate potent fractions of sediment extracts using the H4IIE-luc bioassay, (ii) determine the concentrations of known AhR agonists (polycyclic aromatic hydrocarbons (PAHs) and styrene oligomers (SOs)), (iii) identify previously unreported AhR agonists in fractions by use of GC-QTOFMS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…CHR and methylchrysenes originate from both pyrogenic and petrogenic sources, and methylchrysenes can also be formed from chrysene by bioalkylation. , CHR has previously been found in mollusks, crustaceans, and fish and appears to be diluted in the marine food webs. CHR and its derivatives have been shown to activate rat and human AHR in vitro and to induce Cyp1a activity in desert topminnow (Poeciliopsis lucida) hepatoma cells, and in vivo studies have indicated that CHR can activate both Ahr1 and Ahr2 in zebrafish . Unsubstituted CHR, in the current study, was found to act solely as an agonist of Ahr1a.…”
Section: Discussionmentioning
confidence: 99%
“…CHR and methylchrysenes originate from both pyrogenic and petrogenic sources, and methylchrysenes can also be formed from chrysene by bioalkylation. , CHR has previously been found in mollusks, crustaceans, and fish and appears to be diluted in the marine food webs. CHR and its derivatives have been shown to activate rat and human AHR in vitro and to induce Cyp1a activity in desert topminnow (Poeciliopsis lucida) hepatoma cells, and in vivo studies have indicated that CHR can activate both Ahr1 and Ahr2 in zebrafish . Unsubstituted CHR, in the current study, was found to act solely as an agonist of Ahr1a.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the higher concentrations of PCDD/Fs and dioxin-like PCBs are expected in sediments from inner parts of bays, rivers, and streams. Kim et al (2019b) also reported the newly identified dioxin-like contaminants, such as new polycyclic aromatic hydrocarbons, in sediments from tributaries of Ulsan and Onsan Bays. Our findings indicate the cumulative risks of dioxinlike contaminants to inhabiting species in the sedimentary environments surveyed.…”
Section: Ecotoxicological Implicationsmentioning
confidence: 93%
“…The RePs of AhR-active PAHs are summarized in Table S4. 33,34 VirtualToxLab In Silico Analysis. For compounds without reference compounds, tentative identification was completed using QSAR modeling.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%